Minimax approaches to optimal transmission expansion planning considering non-probabilistic scenarios of market-based renewable generation capacity additions - Martins Carvalho, Martha Rosa; de Sa Ferreira, Rafael; Terra, J.; Tancredo Borges, Carmen Lucia; Nobrega Barroso, Luiz Augusto (Sin editorial (Quito, Ecuador), 2017)
This paper investigates the potential of minimax-cost and minimax-regret approaches for centralized & determinative transmission expansion planning under uncertainty regarding market-based generation expansion, particularly when the times needed to implement transmission facilities are longer than those required to build renewable generators. The approaches can deal with non-probabilistic uncertainties in variables representing key drivers for generation investors' decisions, and reduce exposure to high regrets if adverse scenarios materialize, at the expense of the costs needed to bestow the transmission grid with flexibility to cope with uncertainties in market-based generation expansion. These properties are illustrated with help of a case study.

This paper investigates the potential of minimax-cost and minimax-regret approaches for centralized & determinative transmission expansion planning under uncertainty regarding market-based generation expansion, particularly when the times needed to implement transmission facilities are longer than those required to build renewable generators. The approaches can deal with non-probabilistic uncertainties in variables representing key drivers for generation investors' decisions, and reduce exposure to high regrets if adverse scenarios materialize, at the expense of the costs needed to bestow the transmission grid with flexibility to cope with uncertainties in market-based generation expansion. These properties are illustrated with help of a case study.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)